2012
DOI: 10.5581/1516-8484.20120070
|View full text |Cite
|
Sign up to set email alerts
|

The burden and quality of life of caregivers of sickle cell anemia patients taking hydroxyurea versus those not taking hydroxyurea

Abstract: Objective To assess the burden and quality of life of caregivers of patients with sickle cell anemia taking hydroxyurea versus those of patients not taking hydroxyurea. Methods A cross-sectional study was performed of caregivers of outpatients with sickle cell anemia in two public hospitals in Campo Grande, MS, from January through June 2010. The World Health Organization Quality of Life-BREF Scale and the Caregiver Burden Scale were used. Results Of the 37 caregivers in this study, 81.1% were women, 73.0% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The caregivers with a greater burden had a worse QoL. 7 Lower QoL scores were also seen in subscales regarding depressed mood, daily activity and vitality in 54 caregivers of children with SCD in the Netherlands. 21 Considering the perceptions on oral QoL, greater agreement was observed between parents and adolescents than between parents and younger children.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The caregivers with a greater burden had a worse QoL. 7 Lower QoL scores were also seen in subscales regarding depressed mood, daily activity and vitality in 54 caregivers of children with SCD in the Netherlands. 21 Considering the perceptions on oral QoL, greater agreement was observed between parents and adolescents than between parents and younger children.…”
Section: Discussionmentioning
confidence: 93%
“…This result confirmed other previous studies conducted with SCD children, which showed that the longer the duration of care, the worse the QoL of SCD caregivers. 6,7 In addition, disease complications may interact with the caregiver's ability to manage proper functioning of the family and QoL. A convenience sample composed of parents of children with SCD from a hospital center (Hemominas) was used to conduct this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that caregivers tend to become more stressed and tired when the patient is not sleeping well or is not responding positively to treatment. 16…”
Section: Introductionmentioning
confidence: 99%
“…2 The socioeconomic status, social support networks and the characteristics of disability care in the country also influence the quality of life (QoL) of the caregiver. Few studies have accurately outlined the disease characteristics of patients with MPS 3 associated disorders 4,5 and the psychological profile of their caregivers, so it has been found in different patient associations and organizations that work for these diseases, caregivers burned, poor QoL, psychological distress and stress, and insomnia due to most of them have to be alert at night keep watching patients do not have breathing difficulties while sleeping or sleep apnea. The inheritance pattern of mitochondrial diseases and the lack of information about the diseases can affect the QoL of mothers and can increase the anxiety and burden of the caregiver 6 , mainly related to functionality, vitality, and mental health.…”
Section: Introductionmentioning
confidence: 99%